A nova estrutura romanesca, seu aspecto literário e poético em Manual da paixão solitária, de Moacyr Scliar - Bastos, Clessio Pereira (2013)
This dissertation brings to the reader a study of the evolution of the novel production techniques, involving their new directions, since the late nineteenth century, when the text have left to be a mirror of visible factors to become a sort of magnifying glass that enlarges, for the reader, various aspects of the human perceptions. This research aims to show the route taken by the techniques of literary production and so to examine attentively the current resources used by authors in preparing their narratives in order to place the human being and its key issues at the center of cogitations. To reach this objective, we must reflect on how previous methods were unable to bring the reader into the text, making his or her its coauthor. What was called here new novel resulted from transformations faced by literature, technology and psychoanalysis in the period after the Industrial Revolution, when Sigmund Freud showed with his studies the bottomless pit of human consciousness. Since then, the art undertook itself to deepen this gap in order to set man in his innermost and purest reality. Given this new possibility, Literary Criticism had to change their methods of analysis and to discuss these new forms arising in the current context. Basing on this new building whose component parts include the interior monologue, the stream of consciousness and philosophical aspects relating to language , the novel Manual da paixão solitária, by Moacyr Scliar and Jabuti Award winner in 2009 in the category fiction, served as our object of analysis. Through a skillful "unreading", this book provides a kaleidoscopic view of the story originally found in chapter 38 ofthe Book of Genesis. To achieve this study, we made use of the literary and philosophical reflections by Humphrey (1976), Rosenthal (1974) and Costa (2008), among others, as theorical basis for this research.